Seemingly Unrelated Regression Analysis of Bank Lending and Economic Growth in Nigeria - Agbanike, Tobechi F.; Onwuka, Kevin O.; Enyoghasim, Michael O.; Ikuemonisan, Solomon S.; Ogwuru, H. O. R.; Osigwe, Augustine C. (International Journal of Economics and Financial Issues, 2018)
Using a unique sector-level bank lending and output data sets on the Nigerian economy over the period 1981 to 2014, we examine the impact of bank lending on economic growth, specifically to ascertain whether different sector-level bank lending impact on Nigeria’s economic growth differently. Due to the perceived interrelationships among the sectors, we adopt a seemingly unrelated regression equations (SURE) model consisting of five single equations. The Model was fitted using the seemingly unrelated regression (SUR) estimator. Empirically, we find strong evidence that bank lending to agriculture, industry, real estate and construction and commercial sectors has exerted significant positive impact on economic growth (RGDP) of the respective sectors, thus lending credence to the finance-led-growth hypothesis” in those sectors. Our study further provides evidence that sector-level bank lending impact on Nigeria’s economic growth differently. The highest impact of bank lending is in the agriculture sector, followed by commercial sector, then industrial sector and real estate and construction. However, bank lending does not have any significant impact on economic growth in the service sector. By utilizing sector-level bank lending and output data in our analysis, this study addressed important gap in the relevant literature. It is important for banks to recognize this existence of sectoral differences and to have a proper understanding of sectoral characteristics and therefore, tailor their lending activities in response to sectoral needs. This is critical, especially in our situation where from our analysis, bank lending to agriculture with the highest tendency to impact on economic growth was only about 3 percent of total bank credits during the period covered by the study whereas, bank lending to the service sector (including government services) with no significant impact on economic growth was about 53 percent of total bank credit. Keywords: Bank lending, economic growth, seemingly unrelated regression analysis, Nigeria JEL Classifications: C5, E5, O4